Reacción al texto de Hugo José Suárez. Aportes e implicancias para la marialogía (2025)
The following text offers a reaction to Hugo Suarez's presentation "Popular Religiosity. 50 years of a complex reflection". Taking two of the elements presented by the author-the link between popular religion and everyday life and the consideration of the believer as an analytical unit and construction of meaning-is proposed a theological reflection on some of the contributions and implications that these have for the development of Marialogy.